Atividade prescrita e Atividade realizada: reflexões críticas de uma professora de Inglês - Charlariello, Luciane Nigro (2005)
ABSTRACT This work belongs to the research area Language and Education. It aims to investigate the didatic unit: No violence: It s just a game which was developed by a group of teachers, including the author. These teachers work in Public Schools of São Paulo. This unit was created during the last module of the course Reflection on Action . I set out to examine, explain theoretically and criticize this unit (prescribed activity) and its application (realized activity) and I intend to make suggestions to reconstruct it. In other words, the development of this work will be basically a process of Critic Reflection according to Smith (description, informing, confrontation and reconstruction). The theoretical framework is based on Activity Theory (Vygotsky, 1934/2002, 1924/1984; Leontiev, 1977, 1978, 1998; Engeström, 1987, 1999, 1999a).It is also based on PCNs (1996, 1998) which were discussed with regard to teaching foreign language, sociointeracionism, critical view of teaching-learning and a dialogical perspective of language. This research will be considered a critical one with a collaborative view, because it envolves the combined complex of investigation of action that aims the understanding, analysis and critic of action context aiming to the transformation of this context. The researcher is one of the participants who studies her action context, interferes and transforms her context. The methodology will be a documental analisis (the didatic unit), involving recording classes and transcription (the application of the unit).The data analysis and interpretation suggest that the didatic unit and the classes praise the development of discursive base to discursive engadgement into English language partially, and also the development of critical conscience, and it was based on transversal theme.